Problematic Internet Use: A Longitudinal Study Evaluating Prevalence and Predictors - Megan A. Moreno, MD, MSEd, MPH; Jens Eickhoff, PhD; Qianqian Zhao, MS; Henry N. Young, PhD; Elizabeth D. Cox, PhD (Elsevier, 2019)
Objective: To assess the prevalence over time and predictors of problematic internet use using the Problematic and Risky Internet Use Screening Scale (PRIUSS). We also identified an intermediate-risk PRIUSS score. Study design: In this longitudinal cohort study, we recruited participants using random selection from 2 colleges. Participants completed a yearly PRIUSS. We used multivariate logistic regression analysis to evaluate predictors of problematic internet use. We pursued receiver operating curve analysis to identify an Intermediate risk PRIUSS score. Finally, we applied Markov modeling to test the dynamics of moving through problematic internet use risk states over time. Results: Of 319 participants, 56% were female, 58% were from the Midwest, and 75% were white. Problematic internet use prevalence estimates varied between 9% and 11% over the 4 years. Problematic internet use risk status from the previous time period was identified as the main predictor for problematic internet use (OR 24.1, 95% CI 12.8-45.4, P < .0001). Receiver operating curve analysis identified the optimal threshold for defining Intermediate risk was a PRIUSS score of 15. Conclusions: This longitudinal study of problematic internet use among college students found that risks were present across groups and over time. The most salient predictor of problematic internet use was being at risk at the previous time point. On the basis of these results, we propose a PRIUSS score of 15 as an intermediate-risk cut-off to better identify those at risk of developing problematic internet use.